Organic Growth Improvement of Indonesian Logistics Companies (A Conceptual Model: Contribution of Strategic Management, Transformational Leadership, and Knowledge Management to Corporate Entrepreneurship and Its Impact on Organic Growth) - Sudrajat, Darjat (Bina Nusantara University, 2015)
Indonesian logistics companies needed performance improvement (particularly in organic growth) forÂ increasing their competitiveness. Based on previous researches that in order to increase organic growth, it couldÂ be conducted through developing corporate entrepreneurship, namely the activities that enhance companyâsÂ ability to innovate, take risk and seize market opportunities. The purpose of this paper tried to explore theÂ relationships among variables, namely organic growth (OG), corporate entrepreneurship (CE),Â transformational leadership (TL), knowledge management (KM), and strategic management (SM). Therefore,Â this research used causal-explanatory study to explain relationships among the variables. The results of thisÂ research were concluded that TL, KM, and SM have contributions to corporate entrepreneurship and organicgrowth. The relationships could be constructed in a conceptual model that could be verified through furtherÂ research.